The Impact of Cigarette Consumption and Smoking Duration on the Body Mass Index (BMI) of Students at the Faculty of Agriculture, Methodist University of Indonesia, 2024. - Gabriel Stevani Putri Ndruru; Edwin Anto Pakpahan; Ivonne Situmeang; Endy JuliAnto; Laura Siagian (Jurnal Kedokteran Methodist, 2025)
Background : Smoking is a major global health problem, causing more than 8 million deaths each year 7 million from direct tobacco use and 1.3 million from exposure to secondhand smoke. In Indonesia, the prevalence of smokers aged 10-18 years increased from 7.2% (2013) to 9.1% (2018), making it the third country with the highest number of smokers. Data from the Global Youth Tobacco Survey (2019) shows 40.6% of students aged 13-15 years have used tobacco, with 19.2% currently smoking. Body Mass Index (BMI) is used to assess body weight relative to height. Based on the 2018 Riskesdas, in Indonesia 9.3% were underweight, 55.3% were normal, 13.6% were obese, and 25.8% were obese. Objective: Knowing the impact of the number of cigarettes, the length of smoking and the BMI of students of the Faculty of Agriculture, Methodist University of Indonesia Medan based on the Brikman index in students of the Faculty of Agriculture, University of Indonesia in 2024. Research method: This research is an analytic observational study with a research design using a cross-sectional study. Research results: This study found the most students consuming the number of cigarettes with < 9 cigarettes / day, as many as 37 respondents (46.3%), then smoking duration found 51 respondents (63.7%) with smoking duration < 10 years and Body Mass Index found 28 respondents (35%) with body mass index < 18.5. There is a relationship between the number of cigarettes with Body Mass Index with a p value = 0.045 (p0.05) and there is a relationship between smoking duration with Body Mass Index with a p value of 0.001 (p0.05). The more influential factor is the amount of cigarette consumption with a p value = 0.013 and OR = 2.4. Conclusion: There is a significant relationship between the number of cigarettes and body mass index with a p value = 0.045 and there is a relationship between smoking duration and body mass index with a p value of 0.001.